The Factors Affecting Fraud Prevention in BOS Fund Management (Universitas Negeri Semarang, 2022)
The purpose of this research was to determine the effect and analyze the factors that affect the prevention of fraud in the management of BOS Funds. The method in this research was quantitative method. The sample in this study was schools that received the School Operational Assistance Fund (BOS) in Pekanbaru City, the research respondents were school principals and BOS fund. The sampling technique in this study used a random sampling technique with a total of 74 respondents. The analytical technique used in this study was regression analysis using SPSS version 24. From the results of the partial study, it is known that the SPIP, Organizational Culture, Anti-Fraud Awareness, and Whistleblowing System factors had a positive and significant effect on fraud prevention in the management of BOS Funds.